Isolation and identificationof fungi from outer surface of the insect Red flour beetleTriboliumcastaneum (Herbest) (Coleoptera :Tenebrionidae)andcowpea weevikCallosobruchus maculatus(F.) (Coleoptera :Bruchidae) and the study of some virulence factors in t - ZAINAB HUDHI FARHOOD (Al-Qadisiyah Journal of Pure Science, 2017)
Was isolated 18 Type slept fungi contaminated external surface for 50 samples of the insectRed flour beetleTribolinmcastaneum and 50 samples of the insect cowpea woevCallosobruchusmaculatus collected from the markets of flour and beans were obtained Alihamn local markets in Nasiriyah of DhiQar province, during the months of February and March in 2014 has consisted of eight races are fungi,Mucor, ,Fusarium, RhizopusPaecilomyces,,EmericellaAspergillus,AltarnariaPenicillium.The fungus was more reluctant and is A.flavusby 27.06% and less hesitant fungus is fungus Emericellasp and 2.26% for this insect Red flour beetle, and tested the ability of producing fungi Alafla toxin and analyzed blood laboratory. The results were that all isolates the genus Aspergillus have the ability to secrete Alaflatoxin, either the decomposition of the blood she stated Altnaúj all fungi to break down blood HakablahSepedoniumsp exception was his ability weak